RESEARCH AND THEIR ANALYSIS ON THE TOPIC OF THE ACTIVITIES OF THE TURKIC HAJIBS IN THE SYSTEM OF MANAGEMENT OF THE SOMANID DYNASTY - Abdukamolova Mohlaroy Shuxratjon qizi (Western European Studies, 2024)
The article analyzes the activities of Turkish pilgrims, their role and importance in state administration in the management system of the Somanid power in Movarounnahr and Khorasan of the 9th-10th centuries. The study of the history of the Somanid era began during the Russian Empire and is continued by historians of the Soviet era and other foreign scholars, as well as by Uzbek historians after independence. However, due to the fact that no comprehensive work has been done on the topic we have highlighted, scientific works contain incomplete information. Below, the article examines some of the studies of scientists who provided information that served to reveal the role of Turkish pilgrims and their role in the state importance in the management system of the Somanid government, and shows that it is an actual topic that needs to be fully informed based on specific sources will be passed
Keywords: Somanids; Movarounnahr; Khurasan; historiography